2021
DOI: 10.3389/fmars.2021.693093
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Diagnostic Power of the Internal Transcribed Spacer 2 in Mediterranean and Atlantic Eolid Nudibranchs (Mollusca, Gastropoda)

Abstract: Mediterranean marine biodiversity is still underestimated especially for groups such as nudibranchs. The identification of nudibranchs taxa is challenging because few morphological characters are available and among them chromatic patterns often do not align with species delimitation. Molecular assessments helped unveiling cryptic diversity within nudibranchs and have been mostly based on mitochondrial markers. Fast evolving nuclear markers are much needed to complement phylogenetic and systematic assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…and Favorinidae sp., similarly to what was shown in Cunha et al [25]. The H3 phylogenetic tree (Figure S1) was characterized by a lower resolution, similar to what was shown in previous studies [38][39][40], and the relationships between the S. marhe sequence and other facelinid sequences remained unclear, according to this DNA region. Overall, the results obtained from both morphological and molecular analyses confirmed that the nudibranch belongs to the species S. marhe, the bryozoan to Celleporaria sp., and the hydrozoan to Zanclea sp.…”
Section: Molecular Phylogeneticssupporting
confidence: 82%
See 1 more Smart Citation
“…and Favorinidae sp., similarly to what was shown in Cunha et al [25]. The H3 phylogenetic tree (Figure S1) was characterized by a lower resolution, similar to what was shown in previous studies [38][39][40], and the relationships between the S. marhe sequence and other facelinid sequences remained unclear, according to this DNA region. Overall, the results obtained from both morphological and molecular analyses confirmed that the nudibranch belongs to the species S. marhe, the bryozoan to Celleporaria sp., and the hydrozoan to Zanclea sp.…”
Section: Molecular Phylogeneticssupporting
confidence: 82%
“…Moreover, for the nudibranch, related 16S sequences belonging to the family Facelinidae and the outgroup Duvaucelia odhneri J. Tardy, 1963 (GenBank accession number: OQ145163) were downloaded from GenBank and aligned to our sequence to assess its phylogenetic position. For comparison, a H3 dataset was also assembled and analyzed in the same way, even though this DNA region is known to be weakly informative at the species and genus level [38][39][40]. Sequences were aligned with MAFFT 7.110 [41] with the E-INS-i option; the substitution models were determined using jModelTest 2 [42] under the Akaike Information Criterion, and maximum likelihood phylogenetic analyses were performed with RAxML 8.2.12 [43] with 1000 non-parametric bootstrap replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, two new Eubranchus species were recently described [6], E. viriola and E. andra; however, they should be re-evaluated due to the weak diagnostic characters used by the authors to separate these two species. In fact, E. viriola and E. andra show a 0.15% genetic distance at the Cytochrome Oxidase subunit I (COI) [66], a value that perfectly falls within the range of intraspecific variability accepted for mollusks in general and already demonstrated for nudibranchs [27,69]. The different ecological niches (shallower brackish water for E. viriola and deeper layers characterized by normal oceanic salinity for E. andra [66]) and the distinct color patterns ("the brackish water-living A. viriola sp.…”
Section: Discussionsupporting
confidence: 68%
“…Although genetic divergence in mitochondrial sequences is high and could be delimited as 42 or more Lamellidea species in Hawaiʻi, nuclear ITS2 sequences did not differentiate the multitude of Hawaiian Lamellidea lineages delimited by ASAP. The nuclear ITS2 locus is a fast-evolving locus that has been used to distinguish between closely related species of diverse land snails (Garzia et al, 2021;Prévot et al, 2013;Razkin et al, 2017;Zając et al, 2020), but the phylogenetic tree estimated from pacificelline ITS2 sequences supported a small number of clades. Of the taxa sampled from Hawaiʻi, four clades were supported, recognized here as Lamellidea cylindrica, L. polygnampta, L.…”
Section: Species Delimitationmentioning
confidence: 99%